Land Degradation and Climate in Iceland - a spatial and temporal assessment - Olafsdottir, Rannveig (Department of Physical Geography and Ecosystem Science, Lund University, 2002)
Degradation of vegetation and soil erosion has contributed to loss of biological productivity and land degradation in Iceland. This thesis focuses on spatial and temporal patterns of land degradation in Iceland from a geographical perspective both along short and long timescales. The activity of current degradational processes has been assessed by studying farmers' perception of the problem and comparing it with a spatial analysis of the distributional pattern of severely degraded lands in NE Iceland. Classification of Landsat TM satellite data and an analysis using a digital elevation model in a GIS showed that erosion patches and degraded vegetation had a greater relative distribution at higher elevations, and were more frequent on slopes with a N and NW aspect. These results are interpreted as indicative of the influence of climate on vegetation cover occurring in climatically marginal highland areas. The long-term temporal aspect of land degradation during the Holocene period was investigated using tephrachronological and stratigraphic approaches. Major degradation phases identified occurred c. 5000 BP, c. 2500 BP and from roughly AD 1500-1900 when degradation accelerated to a catastrophic scale. A spatial-temporal picture showing the Holocene vegetational marginal upland areas as highly fluctuating further emerged. So as to assess the long-term influence of climate on the spatial distribution of the vegetation cover, and thus indirectly on the susceptibility of the land to degradation, a temperature-driven dynamic model was developed. The model was used to determine and map the extent of vegetation and birch forest cover for the whole of Iceland throughout the course of the Holocene. Previous assumptions of an extensive forest cover at the time of the Norse settlement in the late 800s were not supported by the model results. Modeling showed that the vegetation and forest cover was already in significant decline prior to the settlement. Anthropogenic influence presumably accelerated and increased a natural ...